Lupus clinical trial eligibility in a real-world setting: results from the British Isles Lupus Assessment Group-Biologics Register (BILAG-BR). Issue 1 (23rd July 2021) - Dyball, Sarah; Collinson, Sophie; Sutton, Emily; McCarthy, Eoghan M; Bruce, Ian N; Parker, Ben
Abstract : Objective: To quantify how well phase III randomised clinical trials in both SLE and lupus nephritis (LN) represents a real-world SLE cohort. Methods: Literature reviews were performed of major published phase III SLE (n=12) and LN (n=6) clinical trials (ClinicalTrials.gov). Inclusion and exclusion criteria common across these trials were collated for non-renal SLE or LN trials, and applied to patients recruited to the British Isles Lupus Assessment Group-Biologics Register (BILAG-BR) starting either biological or standard-of-care (SOC) therapies. Results: We recruited 837 patients to the BILAG-BR from September 2010 to June 2018, starting either SOC (n=125, 15%) or a biological medication (n=712, 85%). Active LN, defined as a BILAG A in the renal domain occurred in 20% (n=166). Overall, 530 (63%) patients were ineligible to participate in non-renal SLE clinical trials and 72 (43%) patients with active LN would be ineligible for LN trials. The most common reasons for ineligibility from the non-renal lupus trials included active renal involvement (n=166, 20%) and low disease activity (n=114, 15%). For LN trials, the most common exclusion met was pre-existing renal impairment (n=15, 9%). Patients with fewer comorbidities were more likely to be eligible to participate in non-renal SLE trials. Conclusions: In this national register of patients with moderate-to-severe SLE, nearly two-thirds would not be eligible for recruitment to key SLE clinical trials nor would almost half of those with active LN. Eligibility criteria may excessively constrain enrolment and thus, how we can generalise trial results in a real-world setting.